On-chip Parallel Photonic Reservoir Computing using Multiple Delay Lines - Hasnain, Syed Ali; Mahapatra, Rabi (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
Silicon-Photonics architectures have enabled high speed hardware implementations of Reservoir Computing (RC). With a delayed feedback reservoir (DFR) model, only one non-linear node can be used to perform RC. However, the delay is often provided by using off-chip fiber optics which is not only space inconvenient but it also becomes architectural bottleneck and hinders to scalability. In this paper, we propose a completely on-chip photonic RC architecture for high performance computing, employing multiple electronically tunable delay lines and micro-ring resonator (MRR) switch for multi-tasking. Proposed architecture provides 84% less error compared to the state-of-the-art standalone architecture in [8] for executing NARMA task. For multi-tasking, the proposed architecture shows 80% better performance than [8]. The architecture outperforms all other proposed architectures as well. The on-chip area and power overhead of proposed architecture due to delay lines and MRR switch are 0.0184mm^2 and 26mW respectively.